Efek economic matter sebagai variabel moderasi terhadap perilaku mengunakan jasa perbankan syariah (sebuah kerangka konseptual) - Asyari Asyari; Perengki Susanto (Jurnal Kajian Manajemen dan Wirausaha, 2023)
This paper is a conceptual framework that was created as a result of earlier scholars' work. It is suggested that the moderating variables perceived risk and profit and loss sharing, which have received little attention from prior researchers. The objective is to gain a deeper understanding of the elements that influence people's views and behavior toward Islamic banking. Examining journals from Emerald Insight, Routledge, Sage, Taylor & Francis, Elsevier/Science direct, and Willey was the strategy utilized to create the conceptual framework. Next, categorize the work by theme and assess it in light of your research focuses. The conclusion of this study includes comments and suggestions for upcoming research topics.